Penataan Jalur Hijau di Surabaya Berdasarkan Karakteristik Jalan dan Kemampuan Visual Pengamat Studi Kasus: Jalan Mastrip Surabaya - Bararatin, Kirami; Hayati, Arina (EMARA Indonesian Journal of Architecture, 2016)
The main streets and the city entrances of Surabaya support its economic activity as well as become a potential to generate first impression or image of the city for its users. In line with the city governments program, the existence of the green line in the corridor of the main streets should be remarked to develop green space. Consequently, Â visual objects on the green line, such as vegetation, need to meet the rules of the visual aesthetic arrangement based on the characteristics of the corridorÂ and visual capabilities of observers. Jalan Mastrip isÂ one of the main streets, which is crucial for the city economy and also becomes a city entrance of Surabaya. It hasÂ potential to give a positive âfirst impressionâ for its users. However, the street condition is still beyondÂ expectation as a city entrance. Therefore, the aim of this study is to formulate the concept of arrangement of green lineÂ in accordance with the characteristics of corridor space and visual capabilities of observers. Descriptive-qualitative method is used supported by the perception of observers / respondents. Then the observations and evaluation results were analyzed to get the arrangement concept of green line of Mastrip corridor, accordance with its characteristics as Surabaya entrance corridor with industry, trade and services concept.